Новый вид семейства Aeolosomatidae (Oligochaeta) из жаберной полости речных раков водоемов Украины - Бошко, Е.Г.; Пашкевичуте, А.С. (Вестник зоологии, 1975)
In the gill cavity of Astacus leptodactylus leptodactylus from the water bodies of the Dnieper and Southern Bug basins Oligochaeta are found which are referred to the new species of the family Aeolosomalidae - Aeolosoma markewitschii sp. n. They affect A. I. leptodactylus most often in the Kakhovka reservoir (91.7%) in 1974. One individual of a host had 1-1241 Oligochaeta, 180.5 specimen on the average.